PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP MINAT BELI PADA MEDIA SOSIAL TIKTOK DEAR ME BEAUTY - Syabatia Nurul Azmi; Indira Rachmawati (Jurnal Ilmiah Global Education, 2023)
Advances in technology introduce various media that can be interpreted as a communication platform, one of which is the internet. There is a main reason users on the Internet is to find information, it provides many opportunities for consumers who rely on eWOM. Tiktok is one of the social media that which functions as a digital marketing platform by Dear Me Beauty. The objective of this research ispfurther study the influence of e-WOM on TikTok towards the intention to buy Dear Me Beauty on TikTok. This research utilize quantitative methods with the aim of descriptive and causal research. Researchers distributed questionnaires through google form with a total of 401 respondents. The sampling techniqueaused was non-probability sampling with purposiveasampling. Data analysis technique utilize Partial Least Square (PLS) Structural Equation Modeling (SEM). The results of this study are the Information Quality has a positive and significant effect on Information Usefulness, the Information Quantity has a positive and significant effect on Information Usefulness, Information Credibility has a positive and significant effect on Information Usefulness. The Usefulness has a positive and significant effect on Information Adoption, and the Information Adoption has a positive and significant effect on Purchase Intention.